Penerapan Metode Resitasi Pembelajaran Daring Terhadap Motivasi dan Hasil Belajar Siswa Secara Mandiri Pada Mata Pelajaran Simulasi Dan Komunikasi Digital Kelas X Teknik Komputer dan Jaringan SMKN 12 Kota Malang - Nadiah Alma Ratnaduhita; Satrio Hadi Wijoyo; Tri Alfrianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Research activities was carried out during the Covid19 pandemic, so learning activities were carried out online. The implementation of the recitation method is carried out during online which aims to make students more independent in understanding and expanding the subject without teacher supervision. The recitation method is an assignment given by the teacher to all students. The research method used is quantitative research with the research type Pre Test-Post Test Control Group Design. The sample in this subject were students of class X Computer Network Engineering 1 as the control class and X Computer Network Engineering 2 as the experimental class with a total of 20 students each class. Research activities carried out using the normality and homogeneity test. In testing the hypothesis using the Wilcoxon and the Mann Whitney test. The results of the normality test showing that the data are not normal, while the homogeneity test results showing that the data are homogeneous. The results of the research hypothesis indicate that there is no difference between each research variables which means that H0 is accepted. The significance value of the hypothesis obtained is 0,356 > 0,05; 0,136 > 0,05; 0,940 > 0,05.